Editorial - Silvera Sarmiento, Astelio; Duque Botero, Cesar Alonso; Silvera Sarmiento, Astelio; Duque Botero, Cesar Alonso; Silvera Sarmiento, Astelio; Duque Botero, Cesar Alonso (Corporación Universitaria Americana, 2023)
The current dynamical social structures imply a huge risk in decision-making, which implies a much more solid level of assertiveness of actions that enable the advancement of knowledge management and the consolidation of a fair and equitable environment.In addition to the emergency of the actual scenario of COVID-19 that put digital tools in the spotlight of the world plus the innovation system of organization management (Restrepo, et al., 2016; Meza, H., et al., 2015; Silvera, et al., 2016), we faced the social inclusion arising as a permanent social necessity in our contemporary society, focusing on this subjectof vulnerability which makes reality of equity and social inclusion a complex transformational phenomenon, more visible while the work on the management of social, cultural and innovative knowledge are able to prepare the right social environment for it